Case Report and Literature Analysis: Guillain-Barré Syndrome With Delayed Unilateral Facial Palsy - Huang, Xuanyu; Lan, Ziwei; Zhan, Yajing; Hu, Zhiping (Frontiers in Neurology, 2021)
Guillain-Barré syndrome (GBS) is an acute inflammatory polyradiculoneuropathy in which most patients have cranial nerve involvement, with facial nerve involvement being the most common. However, delayed facial palsy (DFP) with asymmetric facial palsy is a rare manifestation of GBS, and the mechanism is unclear. We report a case of GBS combined with delayed unilateral facial palsy and review previously reported cases of GBS combined with DFP. A total of 28 cases of GBS with DFP, including the case in this report, were included in this study. The occurrence of DFP may be related to early subclinical demyelination of the facial nerve, the blood-nerve barrier of the facial nerve, facial movement, and descending reversible paralysis. The occurrence of unilateral facial palsy may be related to Campylobacter jejuni, specific anti-ganglioside antibodies, and the site of central nervous system anatomical involvement. There is no evidence that immunotherapy is related to the shortening of DFP course and improving patients’ prognosis.